Perlindungan Hukum Terhadap Tenun Alor dalam Rezim Indikasi Geografis - Lestari Lakalet (Peneliti.net, 2022)
Alor weaving is one of the handicrafts from Alor community whose existence is recognized by hereditary, has different motifs and patterns that are different from woven products from other regions, have a certain philosophy in every motif, and is a Regional Icon that is often promoted in various activities either local, national and international levels. Unfortunately, the products already known to this market have not received legal protection by the State. With the enactment of the Local Government Law, legal protection against geographical indications is part of the responsibilities of the Autonomous Region, therefore the Regional Government should seek guarantees of protection against the potential of regional superior products with geographical indication. This study aimed Knowing the extent of public legal awareness on the importance of legal protection of Intellectual Property Rights. This research was an emperical normative research. Using primary and secondary data, data collection techniques through documentation studies, interviews and qestionnaires using qualitative analysis the Local Government discussed. Based on the discussion then conclusions drawn inductively in response to the problems studied. The results of research indicate that Public awareness of the importance of legal protection of geographical indications of Alor Weaving is very low due to the lack of information they obtain related to the importance of protection of intellectual property law on Alor Weaving.